How do we get them to stay? : exploring the contribution of organisational theories to rural social worker retention within Aotearoa New Zealand’s South Island : a thesis presented in partial fulfilment for the requirements of the degree of Master of Science in Psychology at Massey University, Manawatū, New Zealand - Butler, Andrina May Elizabeth (Massey University, 2025)
Social workers play an integral part in building the safety and security of vulnerable nga tangata. This vulnerability is heighted in rural communities where nga tangata experience geographical isolation and have less access to services than their urban counterparts. It is therefore essential to ensure the long-term retention of rural social workers so our most vulnerable can be supported along their journey of independence. However, there is little research on rural social worker retention in rural settings like NZ. This thesis explored the contribution and relevance of Push-Pull Theory, Social Exchange Theory, Unfolding Theory, Job Embeddedness Theory, Job Characteristics Theory, and Job Demands-Resources Theory to address this literature gap in NZ. Six rural social workers and three leaders of rural social work organisations were interviewed to explore their personal perspectives of their workplace and wider community. Using qualitative, reflexive thematic analysis within a realist epistemology, transcribed interview data revealed themes of community embeddedness, work conditions, and challenges and opportunities. These findings highlighted the importance of both community and workplace embeddedness as described by Job Embeddedness Theory, yet extended on through pulls and pushes, rewards and costs, shocks and adaptability, job design, and demands and resources. Based on these findings, retention strategies should focus on building an understanding of rural social workers as individuals. Organisations can do so by understanding passions, motivations, and characteristics of their staff, which should be on an ongoing basis and not as a one-off or “tick box” exercise. Additionally, organisations must understand the large impact of the community and associated relationships on their social workers, and how personal resources may impact any associated shocks. A highlighted study limitation was that participants discussed their involvement in the study to others, which risked word spreading fast due to their residence in a rural community. Future, similar research should, therefore, include a more in-depth discussion regarding the importance of confidentiality being protected as much by the participant as the researcher, and the additional confidentiality risks from living in a rural community.
Copyright holders of Figures 3, 4 5 & 7 may use the Take Down Request link below to request their removal.
Keywords: 520104 Industrial and organisational psychology (incl. human factors)